1993
DOI: 10.1152/ajpheart.1993.265.1.h340
|View full text |Cite
|
Sign up to set email alerts
|

Limit to cardiac compensation during acute isovolemic hemodilution: influence of coronary stenosis

Abstract: We assessed limit to cardiac compensation during isovolemic hemodilution (HD) in 14 anesthetized dogs. Radioactive microspheres were used to evaluate myocardial blood flow (MBF) and its transmural distribution (endo/epi). Myocardial O2 consumption (MVO2) and percent lactate extraction were determined. Coronary vasodilator reserve was assessed from reactive hyperemic responses. Dogs were divided into group 1, with intact left anterior descending coronary artery (LAD), and group 2, with critical stenosis of LAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 0 publications
5
93
1
10
Order By: Relevance
“…Previous findings from our laboratory have demonstrated a remarkable capacity of the coronary circulation to increase its blood flow during ANH, as needed to maintain myocardial oxygen supply and contractile function. 17,18 Whereas previous studies have suggested a role for reduced viscosity in this response, 24,25 the finding of diminished coronary reactive hyperemic responses shown previously, 17,18 and confirmed herein, implies that coronary vasodilation is also prominently involved.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Previous findings from our laboratory have demonstrated a remarkable capacity of the coronary circulation to increase its blood flow during ANH, as needed to maintain myocardial oxygen supply and contractile function. 17,18 Whereas previous studies have suggested a role for reduced viscosity in this response, 24,25 the finding of diminished coronary reactive hyperemic responses shown previously, 17,18 and confirmed herein, implies that coronary vasodilation is also prominently involved.…”
Section: Discussionsupporting
confidence: 69%
“…Under baseline conditions, the left ventricle extracts approximately 75% of the oxygen that is delivered to it; thus, it has a limited oxygen extraction reserve. 17,22,23 Consequently, to offset the induced decreases in arterial oxygen content, the myocardium is critically dependent on increases in CBF during ANH. Previous findings from our laboratory have demonstrated a remarkable capacity of the coronary circulation to increase its blood flow during ANH, as needed to maintain myocardial oxygen supply and contractile function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nos leitos coronários onde há obstruções críticas, não ocorre o esperado aumento de fluxo sanguíneo, mecanismo responsável pela adaptação miocárdica à anemia. Desta forma, a anemia aguda determina em pacientes coronariopatas rápida instalação de isquemia miocárdica, conforme experimentalmente demonstrado em animais submetidos a hemodiluição normovolêmica (70) . O desbalanço entre a oferta e demanda miocárdica de oxigênio é agravado pelo fato dos próprios mecanismos sistêmicos para adaptação à anemia, anteriormente citados, determinarem maior consumo miocárdico de oxigênio.…”
Section: Anemiaunclassified